Pendampingan Kewirausahaan Desa Berbasis Agro Industri Kelapa Sawit di Desa Bulian Jaya - Ovie Yanti; Musyaiyadah Musyaiyadah; Al Faruk (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
Bulian Jaya Village is an extra-transmigration village of the Bulian I Transmigration Settlement Unit (UPT) under the guidance of the Transmigration Department which was a Central Government program in 1992, this village is an oil palm plantation village. Apart from having extensive oil palm plantation land, in Bulian Jaya Village there is also an oil palm plantation company, namely PT. Inti Indosawit Subur Kebun Muara Bulian. In general, Bulian Jaya Village is a hilly highland area with very extensive plantations. As an independent village that has potential in the field of oil palm plantations, Bulian Jaya Village has many opportunities to improve the economy and welfare of its community through utilizing the potential of existing plantations. This condition makes it very possible to develop entrepreneurship based on the oil palm agro-industry as the main potential possessed by the village. Through this mentoring activity, it is hoped that village entrepreneurship will be formed based on the palm oil agro-industry